2019
DOI: 10.1002/jemt.23411
|View full text |Cite
|
Sign up to set email alerts
|

Microscopy as a tool to investigate the influence of ammonium polyphosphate particle size on the flame retardant properties of polymer composites

Abstract: The influence of ammonium polyphosphate (APP) particle size on the performance of an intumescent formulation and on the synergistic action of a series of montmorillonite samples with different d‐spacings for the production of flame retardant composites was investigated. The polymer matrix employed was poly(ethylene‐co‐butyl acrylate), EBA 30, and the intumescent formulation consisted of APP and pentaerythritol (PER). After being processed, the composites were submitted to scanning electron microscopy (SEM), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…Small particle sizes afford good flame retardancy effect and have little influence on spinning; however, the use of small particles greatly increases the production cost. [30,31] Figure 1 shows the morphology and particle size distribution of MPP and MCA. Both flame retardants have irregularly shaped particles with a particle size ranging between 0.2 and 2 μm.…”
Section: Morphology and Particle Size Of Flame Retardantsmentioning
confidence: 99%
“…Small particle sizes afford good flame retardancy effect and have little influence on spinning; however, the use of small particles greatly increases the production cost. [30,31] Figure 1 shows the morphology and particle size distribution of MPP and MCA. Both flame retardants have irregularly shaped particles with a particle size ranging between 0.2 and 2 μm.…”
Section: Morphology and Particle Size Of Flame Retardantsmentioning
confidence: 99%
“…The behavior of the material under heating and the preservation of the intumescent layer structure were observed by the technique [41]. The analyses were carried out in a Leitz (Oberkochen, Germany) heating microscope (model 1A) and the images were captured by a Samsung SDC 414 ND camera.…”
Section: Heating Microscopy Analysismentioning
confidence: 99%
“…Related studies have investigated the influence of APP/RP flame retardants on flammability. These studies indicated that the combination of APP and RP had a significant synergistic effect that would promote carbon-forming capacity and a dense carbon layer to produce sufficient insulation, further reducing the combustion rate and heat release [29][30][31][32][33]. Yasemin et al [34] investigated the fire performance of LDPE-based composites containing APP and RP.…”
Section: Introductionmentioning
confidence: 99%